2022
DOI: 10.1177/01430343221122387
|View full text |Cite
|
Sign up to set email alerts
|

Do parents have exam anxiety, too? The predictive role of irrational beliefs and perfectionism with parental exam anxiety in explaining students’ exam anxiety

Abstract: Objectives: Exam Anxiety is a condition influenced by both personal and environmental factors as well as cultural, family, and family-related systems. Accordingly, the current study aims at determining the predictive role of parental exam anxiety with irrational beliefs and perfectionism in explaining students’ exam anxiety. Methods: The study included a total of 1006 participants, students (N = 503 (58%) female and (42%) male) and parents (N = 503 (65%) female and (35%) male) of these students. The Test Anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
2
2
0
Order By: Relevance
“…In our study, we found that parents' trait anxiety, school level and school type predicted students' test anxiety (i.e., 9%) above the part of variance explained by various important individual predictors (i.e., stress mindsets, perfectionism, and motivation; 16%). In line withBaytemir et al (2022), our results thus further highlight that parental and school factors matter and may be an interesting additional intervention path to tame students' test anxiety.Our study simultaneously considered multiple individual and contextual factors of students' test anxiety. Among the five parental-level factors, only parent trait anxiety predicted students' test anxiety.…”
supporting
confidence: 84%
See 2 more Smart Citations
“…In our study, we found that parents' trait anxiety, school level and school type predicted students' test anxiety (i.e., 9%) above the part of variance explained by various important individual predictors (i.e., stress mindsets, perfectionism, and motivation; 16%). In line withBaytemir et al (2022), our results thus further highlight that parental and school factors matter and may be an interesting additional intervention path to tame students' test anxiety.Our study simultaneously considered multiple individual and contextual factors of students' test anxiety. Among the five parental-level factors, only parent trait anxiety predicted students' test anxiety.…”
supporting
confidence: 84%
“…A few years later, Baytemir et al (2022) are consistent with the school system structure of Quebec province, which can generate differences in the school environments between public and private schools, as well as elementary and high schools. In the past decades, the offer of enriched programs has significantly increased in the Quebec school market, where attending enriched programs or private schools has led to higher education attainment levels for students (Frenette & Chan, 2015).…”
Section: Contextual Factors Matter For Youth's Test Anxietysupporting
confidence: 64%
See 1 more Smart Citation
“…'B' mentions to irrational beliefs, whereas 'C' denotes to the behavioral and psychological consequences of irrational beliefs like maladaptive behavior and psychological disturbance. Inside this context, 'D' mention to the therapeutic procedure of disputing the irrational beliefs and 'E' refers to the effect, where changing and adapting rational beliefs and following decline in maladaptive psychological symptoms and behaviors (Bernard & DiGiuseppe, 1989;Baytemir, 2023).…”
mentioning
confidence: 99%